2006
DOI: 10.3758/bf03193821
|View full text |Cite
|
Sign up to set email alerts
|

Top-down and bottom-up sequential modulations of congruency effects

Abstract: Several studies have demonstrated reduced congruency effects after incongruent trials. The conflict monitoring hypothesis (Botvinick, Braver, Barch, Carter, & Cohen, 2001) assumes that this sequential modulation is based on top-down cognitive control and suggests that more control is engaged after the detection of conflict. An alternative account is based on repetition effects of stimulus and response features and can be considered bottom up. This study investigates both modulatory sources. In a Stroop task wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
145
4
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(165 citation statements)
references
References 33 publications
15
145
4
1
Order By: Relevance
“…The distinction between slow and fast pace is particularly important for the interpretation of neuroimaging studies, which in general have used long intertrial intervals, as required by technical constraints in extracting the hemodynamic signal. However, differences in intertrial interval cannot provide a full explanation, as some studies have found a trial-to-trial modulation in the absence of repetition priming, even at short intervals (Notebaert et al, 2006). Although dynamic cross-task trial-to-trial modulation of cognitive control was absent in Experiment 1, a sustained increase in top-down regulation was observed in Experiment 2; congruency effect was reduced in blocks with a high ratio of incongruent-to-congruent trials.…”
Section: Discussionmentioning
confidence: 73%
“…The distinction between slow and fast pace is particularly important for the interpretation of neuroimaging studies, which in general have used long intertrial intervals, as required by technical constraints in extracting the hemodynamic signal. However, differences in intertrial interval cannot provide a full explanation, as some studies have found a trial-to-trial modulation in the absence of repetition priming, even at short intervals (Notebaert et al, 2006). Although dynamic cross-task trial-to-trial modulation of cognitive control was absent in Experiment 1, a sustained increase in top-down regulation was observed in Experiment 2; congruency effect was reduced in blocks with a high ratio of incongruent-to-congruent trials.…”
Section: Discussionmentioning
confidence: 73%
“…In one case, reliable amounts of sequential modulation were observed when trials alternated between two different tasks (Freitas et al, 2007); in another case, reliable sequential modulation was observed in a novel task that combined elements of the spatial version of the Stroop task and temporal flankers (Kunde & Wühr, 2006). Demonstrations of significant sequential modulation have also occurred when congruence was at chance and mostbut not all-of the repetition confounds were controlled (e.g., Notebaert et al, 2006). Clearly, more research is necessary.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, the feature integration account is a viable account of the sequential modulations in the Simon effect (Notebaert et al, 2001). 1 To dissociate the contributions of the two processes, Notebaert, Gevers, Verbruggen, and Liefooghe (2006) used a three-choice Stroop task with two different response-stimulus intervals (RSIs). They hypothesized that conflict monitoring would take time to exert its effect on performance on the subsequent trial because it was a "top-down" process.…”
Section: Two Accounts Of Sequential Effectsmentioning
confidence: 99%